Dying for Leave: How Societal Views on End-of-Life Care Pushed Ballard to Expand the Meaning of Care Under the Family and Medical Leave Act - Katherine Vaky (Washington University Law Review, 2017)
The Seventh Circuit’s recent decision in Ballard v. Chicago Park District shook employers and employment law attorneys to their core, forcing reevaluation of what it means to care for a family member with a serious medical condition under the Family and Medical Leave Act (FMLA). Ballard, a former employee of the Chicago Park District, requested FMLA leave to take her terminally-ill mother on vacation to Las Vegas as part of her mother’s end-of-life plan, constructed by her mother and her mother’s hospice team. The Seventh Circuit agreed with Ballard that her employer should have granted FMLA leave for the trip. In fact, Ballard created a circuit split on the issue,6 placing the Seventh Circuit at odds with the First and Ninth on the meaning of care in the context of traveling. By holding that an employer improperly denied FMLA leave to an employee accompanying her dying mother on a Las Vegas vacation, the Seventh Circuit stretched the FMLA’s meaning of care when applied to a seriously ill family member. Ballard expanded the meaning of care by finding aspects of end-of-life care acceptable as caregiving activities. The unique facts of this case and the court’s emphasis on the nature of the mother’s terminal illness introduce the subtle notion that the meaning of care loosens when applied to a dying family member. This case creates a lower threshold that was likely not intended by Congress and will frustrate employers, but is very much in line with American values and societal norms regarding end-of-life care. This Note analyzes the Seventh Circuit’s interpretation of FMLA care in Ballard. Part II provides an overview of the FMLA, focusing on the family-member-care provision, and various judicial interpretations of this provision. Part III explains the facts and judicial rationale in Ballard. Then, Part IV analyzes societal and congressional views of end-of-life care. Finally, Part V of this Note explores the significance of the Ballard decision and the risk of employee abuse. While the FMLA does not distinguish or discriminate on its face between a seriously ill family member and a dying one, this Note explores how the definition of care likely becomes more flexible if the employee requests FMLA leave to tend to a terminally ill family member. This flexibility will have a huge impact as the largest generation begins to depart while under the care of employed, younger family members. While Congress likely did not intend the FMLA’s meaning of care to be taken so far, Ballard’s expansion of the meaning of care is well in line with other legislative actions addressing elderly care and societal views that the dying deserve the best care, even beyond what medicine can provide.
Keywords: FMLA; Ballard; end of life care; values; illness; healthcare; employment; terminally-ill